Clinical pregnancy outcomes in young women with diminished ovarian reserve undergoing frozen embryo transfer: a comprehensive analysis with exploratory insights into endometrial aging - Liu, Feng-xia; Ming, Hui-xin; Huang, Ka-li; Yi, Shan-jia; Liang, Xue-fei; Luo, Wei-wei; Shi, Ming-hua (Frontiers in Endocrinology, 2025)
IntroductionThis study compared pregnancy outcomes after frozen-thawed embryo transfer (FET) in infertile women aged <40 years with diminished ovarian reserve (DOR) versus normal ovarian reserve (NOR), incorporating exploratory analysis of potential endometrial aging factors.MethodsIn this retrospective study, we analyzed the data of 1,362 patients aged <40 years who underwent FET between January and December 2024. Patients were categorized into two groups: the DOR (anti-Müllerian hormone [AMH] < 1.1 ng/mL, n = 136) and NOR (AMH ≥ 1.1 ng/mL, n = 1,226) groups. Pregnancy outcomes were compared after adjusting for confounding factors using inverse probability weighting. Additionally, exploratory immunohistochemical analysis of p16 expression was performed using endometrial samples from 16 patients (n = 8 per group).ResultsAfter weighting, the clinical pregnancy rate was significantly lower in the DOR group than in the NOR group (47.0% vs. 58.3%, P = 0.040; odds ratio = 0.63, 95% confidence interval: 0.41–0.98). Exploratory analysis revealed that the expression of p16 was significantly higher in the endometrial cells of patients with DOR than in those of patients in the NOR group (P < 0.001). Furthermore, a trend toward lower clinical pregnancy rates was observed with higher p16 expression.ConclusionThese exploratory findings suggest that reduced pregnancy rates in young women with DOR may involve endometrial aging mechanisms; however, the preliminary nature and limited sample size for molecular analysis necessitate cautious interpretation and warrant validation in larger and well-controlled cohorts.